Exergy analysis of a Naturally Ventilated Building Integrated Photovoltaic (BIPV) System - Agathokleous, Rafaela; Kalogirou, Soteris A.; Karellas, Sotirios (My University, 2016)
The integration of PV panels in a second skin creates heat behind the PVs, which if not removed it lowers the efficiency of the PV panels because of the high temperature. Consequently, it is important to find the configuration of the system that will increase the efficiency of the PVs and do not increase the cooling loads of the building in summer. For this study, various experiments were carried out to test the temperature distribution of a naturally ventilated system in terms of the inclination angle, solar radiation and the air gap width. The results concern temperature of the PVs and air flow rate. However, in order to examine the performance of the Building Integrated Photovoltaic (BIPV) systems, energy and exergy analyses should be done simultaneously since energy describes the quantity of energy while exergy represents the quality of energy. In this study an exergy analysis is used in order to find the configuration at which the system performs better.
Keywords: BIPV; Exergy; Photovoltaics; Thermal behaviour; Natural ventilation